2015
DOI: 10.1177/0394632015617069
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL-17A concentration and effector functions of peripheral blood neutrophils in food allergy hypersensitivity patients

Abstract: Lymphocytes Th17 and other types of immune system cells produce IL17. By induction of cytokines and chemokines, the IL17 cytokine is involved in mechanisms of allergic reaction with participation of neutrophil granulocytes. It affects activation, recruitment, and migration of neutrophils to the tissues, regulating inflammatory reaction intensity. Excited neutrophils secrete inter alia elastase and reactive oxygen species (ROS)--significant mediators of inflammation process responsible for tissues damage.The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…A recent study has shown that neutrophils are activated in the early stage of acute human anaphylaxis [16]. Previous studies conducted by the authors of this study confirmed that neutrophils are rapidly activated during allergic food hypersensitivity and are important elements of non-specific immune response [17]. These studies suggest a potential VIT [20,21].…”
Section: Discussionsupporting
confidence: 73%
“…A recent study has shown that neutrophils are activated in the early stage of acute human anaphylaxis [16]. Previous studies conducted by the authors of this study confirmed that neutrophils are rapidly activated during allergic food hypersensitivity and are important elements of non-specific immune response [17]. These studies suggest a potential VIT [20,21].…”
Section: Discussionsupporting
confidence: 73%
“…Most of the cytokines levels on day 90 in this patient were ≤2-fold different from the average levels of all course 4 AR patients. One exception was IL-17A, a cytokine known to be associated with food allergy ( 16 ). The IL-17A levels in this patient (4.02 ± 0.14) were higher than 29 of 32 (91%) patients who did not have any AR.…”
Section: Resultsmentioning
confidence: 99%
“…This interleukin family consists of IL-17, IL-17B, IL-17C, IL-17D, IL-17E (also called IL-25) and IL-17F. IL-17E/ IL-25 is produced by mast cells, Th2 cells, eosinophils, basophils, alveolar macrophages, microglia, epithelial and endothelial cells [33,34]. There are many studies indicating that IL-17E/IL-25 plays an important role in the pathogenesis of allergic diseases [35,36].…”
Section: Discussionmentioning
confidence: 99%